2019
DOI: 10.1017/wet.2018.102
|View full text |Cite
|
Sign up to set email alerts
|

Control of Atrazine-Resistant Palmer Amaranth (Amaranthus palmeri) in Double-Crop Grain Sorghum

Abstract: Double-crop grain sorghum after winter wheat harvest is a common cropping system in the southern plains region. Palmer amaranth is a troublesome weed in double-crop grain sorghum in Kansas. Populations resistant to various herbicides (e.g., atrazine, glyphosate, metsulfuron, pyrasulfotole) have made Palmer amaranth management even more difficult for producers. To evaluate control of atrazine-resistant and atrazine-susceptible Palmer amaranth in double-crop grain sorghum, we assessed 14 herbicide programs, of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 24 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…For example, atrazine + S ‐metolachlor + mesotrione increased the odds of successful waterhemp control by 458% (CI 2.62 to 11.92), whereas the odds of successful giant foxtail control increased by 114% (CI 1.33 to 3.43) compared with the individual herbicides alone. In previous studies comparing efficacy across seven or fewer environments, combinations of atrazine, acetochlor, S ‐metolachlor, and mesotrione often achieved greater control of common lambsquarters, giant foxtail, and waterhemp than that of the herbicides applied alone 13,35,36 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, atrazine + S ‐metolachlor + mesotrione increased the odds of successful waterhemp control by 458% (CI 2.62 to 11.92), whereas the odds of successful giant foxtail control increased by 114% (CI 1.33 to 3.43) compared with the individual herbicides alone. In previous studies comparing efficacy across seven or fewer environments, combinations of atrazine, acetochlor, S ‐metolachlor, and mesotrione often achieved greater control of common lambsquarters, giant foxtail, and waterhemp than that of the herbicides applied alone 13,35,36 …”
Section: Resultsmentioning
confidence: 99%
“…In previous studies comparing efficacy across seven or fewer environments, combinations of atrazine, acetochlor, S-metolachlor, and mesotrione often achieved greater control of common lambsquarters, giant foxtail, and waterhemp than that of the herbicides applied alone. 13,35,36 To prevent corn yield loss from weed interference, weeds must be controlled typically between emergence and the eight-leaf stage in corn. 37,38 To accomplish this, PRE herbicides and herbicide combinations are often used to control early-emerging weeds and increase the efficacy of subsequent chemical or mechanical weed control methods.…”
Section: Overcoming Weather Variability With Herbicide Combinations?mentioning
confidence: 99%
“…Amaranthus palmeri populations have expanded well beyond their original native range in the southwestern United States and northern Mexico (Roberts and Florentine 2022;Ward et al 2013). This expansion was facilitated by natural and human mechanisms, including migratory waterfowl, native seed mixes for conservation plantings, and other agricultural practices (Bagavathiannan and Norsworthy 2016;Farmer et al 2017;Hartzler and Anderson 2016). The expansion of A. palmeri is also global, with populations in Africa, Asia, Europe, Oceania, and South America (Kistner and Hatfield 2018;Küpper et al 2017;Mennan et al 2021;Milani et al 2021;Sukhorukov et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In Iowa, the first reported sighting of A. palmeri occurred in 2013 in Harrison County, located less than 10 km from the Missouri River and Nebraska (Hartzler and Anderson 2016). The field had been fallow for the spreading of waste from a fermentation plant in southern Nebraska, a region where A. palmeri was present.…”
Section: Introductionmentioning
confidence: 99%
“…A density of 10 plants m -1 resulted in a soybean yield reduction of 68% (Klingaman and Oliver, 1994). Studies have demonstrated that Palmer amaranth caused economic yield loss in many other crop species, including cotton (Berger et al, 2015;Norsworthy et al, 2014), corn (Massinga et al, 2001;Massinga and Currie, 2002;Wiggins et al, 2015), and sorghum (Besançon et al, 2017;Hay et al, 2019).…”
mentioning
confidence: 99%